PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIE SMP NEGERI 40 PEKANBARU - Tilla, Azifa; Solfitri, Titi; Anggraini, Rini Dian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is classroom action research that aims to improve learning process and to increase mathematics achievement with applied the learning model of Problem Based Learning. The subject of this research is student of class VIIE SMP Negeri 40 Pekanbaru in academic years 2018/2019, which amounted to 39 students, consist of 22 boys and 17 girls Aritmetika Sosial form material. The research consist of two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection. The instrument of data collection in this research consist of observation sheet and assessment sheet. Data collection techniques in this study consisted of observation techniques and test results of mathematics learning techniques. Data obtained from the observation sheet is qualitative data and analyzed by descriptive quantitative analysis technique. Data obtained from the learning result test were analyzed by descriptive statistical analysis technique. The result of data analysis show teacher’s and student’s activity have been done very well in cycle II and weakness/deficiency that happened less from cycle I to cycle II. Most of students were very confidenced and actived in learning process, such as while they were finished mathemathic’s problems that given, presenting the result of problems and giving the conclusion of learning.The results of this research showed the number of students that reach Minimum Mastery Criteria (KKM) for knowledge increase from the basic score (28,21%) to (35,89%) at the first test and to (74,36%) at the second test. For the skills, the score increase from (28,21%) at the first test, to (69,23%) at the second test. The results of this research showed that application of Problem Based Learning can improve the learning process and increase mathematics outcomes for students VIIE SMP Negeri 40 Pekanbaru in 2018/2019 academic year at Aritmetika Sosial form material.Key Words: Mathematics Learning Outcomes, Problem Based Learning, Class Action Research